2018
DOI: 10.4236/jbm.2018.64003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets of Curcumin and Future Therapeutic Role in Leukemia

Abstract: Leukemia is a most prevalent type of cancer around the globe. Due to major side effects of Chemotherapy and radiotherapy, scientists worked to explore the alternative source to treat leukemia. An alternative source for the treatment of leukemia existed in the form of curcumin, a natural phenolic compound extracted from curcuma longa plant. It exhibited anticancer properties reducing the tumor load via apoptosis and cell cycle arrested in various cancer cell lines and controlled tumor proliferation by blocking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Because several antioxidants stimulate apoptotic pathways and chemotherapy also induces apoptosis by harming DNA, complementary effects between chemotherapeutics and antioxidants exist [94]. The polyphenols, resveratrol, and curcumin exhibit prooxidant and antioxidant effects, whether in combination with other natural antioxidants or classical chemotherapy and may be promising future strategies in chemoprevention and chemotherapy of hematological malignancies [102,103].…”
Section: The Antioxidant Approachmentioning
confidence: 99%
“…Because several antioxidants stimulate apoptotic pathways and chemotherapy also induces apoptosis by harming DNA, complementary effects between chemotherapeutics and antioxidants exist [94]. The polyphenols, resveratrol, and curcumin exhibit prooxidant and antioxidant effects, whether in combination with other natural antioxidants or classical chemotherapy and may be promising future strategies in chemoprevention and chemotherapy of hematological malignancies [102,103].…”
Section: The Antioxidant Approachmentioning
confidence: 99%
“…p21 is one of the downstream genes that are being transactivated by p53 90. In fact, curcumin activates p53 directly which repairs DNA and it also inactivates serine/threonine-specific protein kinase (Akt) which resulted in increased expression of Bax gene and induction of apoptosis 91,92…”
Section: Introductionmentioning
confidence: 99%
“…And with the increased dose of CUR, the expression of P‐gp decreased, and the effective blood concentration of DDP increased. Some studies showed that NF‐κB was the target of CUR to reverse MDR in cancer (Allegra et al, 2017; Rafiq et al, 2018). Ye, Yan, et al (2012) found that MDR in lung cancer cells was mainly associated with two pathways.…”
Section: Application Of Cur In Tumor Mdrmentioning
confidence: 99%